4‐Methylumbelliferone treatment and hyaluronan inhibition as a therapeutic strategy for chronic prostatitis. Issue 14 (28th July 2021) - Chen, Jing; Meng, Jialin; Jin, Chen; Mo, Fan; Ding, Yang; Gao, Xiaomei; Zhang, Li; Zhang, Meng; Liang, Chaozhao
Abstract: Background: Hyaluronan (HA), an extracellular matrix component, accumulates in most chronic inflammatory tissues. Here, we studied the impact of HA on the pathogenesis of chronic prostatitis. Materials and Methods: First, we sorted demographic characteristics and peripheral blood serum samples from patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) to assess the relationship between the levels of HA in peripheral blood serum and the severity of inflammation in patients. Second, we induced an experimental autoimmune prostatitis (EAP) mouse model and treated the mice with 4‐methylumbelliferone (4‐MU) (200 mg/kg/day). After the mice were sacrificed, RNA from Th1 cells of the mouse spleens was extracted for RNA sequencing. We used weighted gene co‐expression network analysis (WGCNA) to identify co‐expressed gene modules and hub‐gene related to the pathogenesis of EAP. The expression of critical genes associated with the identified pathway was confirmed by using western blot analysis. Results: HA was significantly more highly expressed in CP/CPPS patients than in healthy volunteers and positively correlated with the severity of pain, urination symptoms, and quality of life. Besides, the protein expression of HA was significantly higher in prostate tissues derived from EAP models than in those derived from controls. 4‐MU, an oral inhibitor of HA synthesis, relieved immunocyte infiltration to the prostate and significantly reduced the proportion of Th1 cells. Based on the WGCNA, we identified 18 co‐expression modules and identified that the Grey60 and brown modules were positively associated with the EAP and negatively associated with the Control and 4‐MU‐treated groups. Pathway enrichment analyses and western blot assays proved that HA potentially activated the cell cycle pathway, increasing the proportion of Th1 cells promoting chronic prostatitis pathogenesis, while these processes were reversed by 4‐MU treatment. Conclusions: Our results suggest that HA is elevated in patients with CP/CPPS compared with healthy controls and that targeting HA through 4‐MU suppresses the activity of the cell cycle‐related pathway, potentially by decreasing the proportion of Th1 cells and relieving chronic prostatitis. Our findings might inspire the clinical treatment of chronic prostatitis.